ANALISIS KOMPARASI IMAM MALIKI DAN IMAM SYAFI’I DALAM IBADAH SEHARI-HARI : Studi tentang Thoharoh, Wudlu, Tayamum dan Mandi - Jazari (Jurnal Studi Pesantren, 2022)
The difference between ulama in responding to the determination of the law of daily worship is very interesting to study. Differences of opinion between Imam Maliki and Imam Shafi'i are very interesting to discuss, among others, in daily halibadah such as thoharoh, unclean objects and how to purify them, how to do and do syata pillars of performing ablution and tayammum, and bathing. comparison of Imam Maliki and Imam Shafi'i in daily worship. The method used in this research is the library research method with a qualitative approach. This research is concerned with cases of daily worship law from the point of view of the Maliki and Shafi'i schools. There were differences of opinion regarding the interpretation of one assembly. thoharoh, unclean objects, ablution, bathing, menstruation and istihadhoh. Keywords: Comparison, Imam Maliki, Imam Syafi'i